Efficiency measurement of tourist organizations - Béres-Virág, Ágnes (Studia Mundi – Economica, 2018)
The development based on management of different settlements, regions as destinations have significant role in the tourism of Hungary. Over the past decade several tourist organizations have been established which involve a variety of tourist stakeholders. Numerous international and domestic researches have also dealt with the cooperation of tourist areas and their competitiveness and sustainability but less attention was paid to the efficiency of the tourist organizations. The purpose of the study was to evaluate the practical assessment and implementation of efficiency measurement, which can improve the operation of the internal trust network.